Areas of Vocational Education Research
IX, 274 p. 8 illus.
Keywords: This book provides an overview of some fundamental topics of international Technical and Vocational Education and Training (TVET), e.g. genesis of TVET research, fields of TVET research, curriculum development, TVET planning and developing, methods of TVET research etc. The International Handbook of Technical and Vocational Education and Training Research (Rauner/Maclean), published in 2009 by Springer, was the first handbook to provide a comprehensive coverage of TVET research in an international context and with a special focus on research and research methods. Building upon the great success of this handbook and replying to the great demand expressed by researchers, (postgraduate) students and decision makers in VET, this new book “Areas of Vocational Education Research” focuses on providing an easier accessible overview of the fundamental topics of international TVET research.